Developing a star rating system for guesthouses to promote budget tourism in the Maldives: An exploratory study - Philip Pong Weng Wong; Uzain Mohamed (School of Tourism, Universitas Ciputra Surabaya, 2022)
The Maldives is a Small-Island Developing State (SIDS) in the Indian Ocean and is a destination synonymous with luxury tropical tourism. Due to its strong competitive advantage in terms of its natural attractions (sun, sea, and sand), Maldives has become one of the most expensive tropical island tourism destination in the world. However, the majority of the benefactors of the Maldivian tourism industry are the large, international hotel chains and franchises while the average Maldivian is not getting a fair share of the tourism receipts. To ensure that tourism revenue are more evenly distributed, the Maldivian government encouraged the setting up of guesthouses as a small-medium enterprise initiative that would help the local economy. However, statistics show that while there are more guesthouses than resorts in Maldives, the average occupancy in guesthouses is much lower than the luxury resorts. This study aims to explore the feasibility of introducing a star-rating system for the burgeoning guesthouse industry in the Maldives to improve the quality and image of their product offerings so that the business potential of this tourist accommodation sector can be realized. Results from semi-structured interviews with guesthouses’ owners, visitors, industry professionals and government officials shows that most stakeholders are favor of a quality control system for the guesthouses and it is recommended that a star-rating system based on the SERVQUAL model be introduced as a suitable method for evaluating their service quality.